โมเดลสมการโครงสร้างเชาวน์ปัญญา ความฉลาดทางอารมณ์ ความคิดสร้างสรรค์ กลยุทธ์ในการศึกษาและการเรียนรู้ และผลสัมฤทธิ์ทางการเรียนของนิสิตระดับปริญญาบัณฑิต จุฬาลงกรณ์มหาวิทยาลัย - มีนมาลย์ สุภาผล (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this research were to develop the structural equation model of intelligence quotient, emotional intelligence, creative thinking, learning and study strategy and academic achievement, to examine the goodness of fitting of the model to the empirical data, and to test invariance of the model of the effectiveness of different science. The research sample consisted of 720 undergraduate students, Chulalongkorn University; the variables consisted of two endogenous latent variables: learning and study strategy and academic achievement; and three exogenous latent variables: intelligence quotient, emotional intelligence and creative thinking. These latent variables were measure by 18 observed variables. Data were collected by Advanced Progressive Matrices-APM, Torrance Test of Creative Thinking Figural Form A, testing of emotional intelligence and testing of learning and study strategy having reliability from 0.64-0.99 and analyzed by using descriptive statistics, Pearson s product moment correlation, LISREL analysis and multiple group structural equation model analysis. The major findings were as follows: 1. Correlation coefficient between latent variable having between 0.002-0.825. These latent variables are positively correlated. Correlation coefficient between learning and study strategy with academic achievement (0.825) learning and study strategy with emotional intelligence (0.658) 2. The structural equation model showed that variable having maximum direct effect to academic achievement was learning and study strategies and variable having maximum total effect was emotional intelligence through learning and study strategy. 3. The structural equation model was valid and fit to the empirical data. The model indicated that the Chi-square goodness of fit to test was 55.27, p = 0.687, df = 58, GFI = 0.990, AGFI = 0.973 and RMR = 0.103 the model accounted for 84.4% of variance in effectiveness of academic achievement. The structural equation model indicated invariance of model form among two different sciences. The structural equation model indicated that the Chi-square goodness of fit test was 107.21, p = 0.449, df = 106, GFI = 0.975, NFI = 0.979, RFI = 0.945 and RMR = 0.141. But the tested parameters were not invariant among 2 fields of study.